2007
DOI: 10.1111/j.1475-1313.2006.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of myopia and hyperopia in a population of Polish schoolchildren

Abstract: Purpose: The aim of this study was to determine the prevalence of myopia and hyperopia in a population of Polish schoolchildren. Methods: A total of 4422 students were examined (2107 boys and 2315 girls, aged 6-18 years, mean age 11.1, S.D. 3.5). The examination included retinoscopy under cycloplegia induced with 1% tropicamide. Myopia was defined as a spherical equivalent (SE) of at least )0.5 dioptres (D), and hyperopia as a SE of at least +1.0 D. Data analysis was performed using Spearman's rank correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
55
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 29 publications
(130 reference statements)
12
55
1
2
Order By: Relevance
“…10 A similar study in Poland also showed a large difference of myopia prevalence between urban (13.9%) and rural (7.5%) children. 24 Unlike previous studies, we did not find a large difference between rural and urban areas of Korea. This finding could be due to exceptionally high educational pressures in South Korea, which is supported by the fact that even in this rural area, over 50% of young males are enrolled in 4-to 6-year university programs, and also the evidence that South Korea is one of the top countries in international educational surveys such as Program for International Student Assessment carried out by the Organisation for Economic Co-operation and Development.…”
Section: Discussioncontrasting
confidence: 76%
“…10 A similar study in Poland also showed a large difference of myopia prevalence between urban (13.9%) and rural (7.5%) children. 24 Unlike previous studies, we did not find a large difference between rural and urban areas of Korea. This finding could be due to exceptionally high educational pressures in South Korea, which is supported by the fact that even in this rural area, over 50% of young males are enrolled in 4-to 6-year university programs, and also the evidence that South Korea is one of the top countries in international educational surveys such as Program for International Student Assessment carried out by the Organisation for Economic Co-operation and Development.…”
Section: Discussioncontrasting
confidence: 76%
“…The study population in Northern Ireland is slightly older than that of the Australian study (mean age: 13.1 vs 12.7 years, respectively), but this difference is unlikely to fully explain the disparity in reported prevalences. A lower prevalence of myopia (11% in 13-year-old children) has also been reported in Poland, with 1% tropicamide used as the cycloplegic agent 20. By contrast, the prevalence of myopia in Northern Ireland is markedly lower at 12–13 years than the 45% reported in Swedish children of the same age 21.…”
Section: Discussionmentioning
confidence: 85%
“…However, many older, urban youngsters particularly do not wear spectacles, even though they need them (Holguin et al, 2006;Yawn, Kurland, Butterfield, & Johnson, 1998;Zeng et al, 2009). In fact, older children/adolescents have more myopia (Czepita et al, 2007;Holguin et al, 2006;Murthy et al, 2002). A main reason reported for dissatisfaction with spectacles is the preference of not wearing them or using contact lenses (Li et al, 2009;Walline et al, 2005;Yawn et al, 1998), even when researchers used fashionable glasses (Zeng et al, 2009).…”
Section: Effect Of Glasses On the Children Who Wear Themmentioning
confidence: 93%